BS EN 15269-3. Extended application of test results for fire resistance and/or smoke control for door, shutter and openable window assemblies, including their elements of building hardware. Part 3. Fire resistance of hinged and pivoted timber doorsets and openable timber framed windows (15th October 2020) - British Standards Institution,
No abstract available